Investment Policy Strategies in Risk and Liquidity Management for DualAccount Old-Age Security Schemes - Rahmawati, Nurul; Indrawan, Raden Dikky; Asikin, Zenal (Asian Journal of Social and Humanities, 2025)
This study aims to formulate an optimal investment policy for the Dual-Account Old-Age Savings (JHT) program managed by BPJS Ketenagakerjaan. The surge in early withdrawals since 2020 has shifted JHT’s role from long-term savings to a short-term liquidity instrument, creating potential asset–liability mismatches. The Asset Liability Management (ALM) framework is applied to assess asset–liability alignment, while the Modern Portfolio Theory (MPT) ensures efficient risk–return trade-offs. Strategy prioritization employs the Analytical Hierarchy Process (AHP) with 10 experts and five key criteria. The results indicate Asset–Liability Balance (0.25) and Liquidity (0.24) as dominant factors. The 70:30 allocation (Main:Supplementary Account) is identified as the optimal strategy (weight 0.67), balancing short-term liquidity resilience and long-term fund sustainability, consistent with ALM–MPT principles and post-P2SK policy direction